The phenomenon of "civil religion" in the verification of Ukrainian and world religious thought - Yuriy Vil’khovy (Українське Pелігієзнавство, 2015)
The article reviews the works of Ukrainian and foreign researchers, the object of which was the phenomenon of «civil religion» in the context of harmonization of relations between church, state and society